2006
DOI: 10.2214/ajr.04.1708
|View full text |Cite
|
Sign up to set email alerts
|

Impact of CT-Guided Drainage in the Treatment of Diverticular Abscesses: Size Matters

Abstract: Patients with abscesses smaller than 3 cm in size can be treated with antibiotics alone and, in some cases, as outpatients, and may not uniformly require surgery. This is also likely true for patients with abscesses 3-4 cm in size, although our results in this group were limited by a small sample size. Patients with abscesses larger than or equal to 4 cm can be managed with CT-guided abscess drainage followed by referral for surgical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
113
0
10

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(126 citation statements)
references
References 27 publications
3
113
0
10
Order By: Relevance
“…In the case of smaller abscesses that cannot be reliably punctured, daily inflammation monitoring and conservative therapy should be performed. According to the literature, abscesses can be detected on computed tomography in approximately 15 % of patients with acute diverticulitis [39,40]. In the case of larger abscesses > 4 cm, abscess drainage in combination with antibiotic therapy should be performed to prevent the need for emergency surgery.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of smaller abscesses that cannot be reliably punctured, daily inflammation monitoring and conservative therapy should be performed. According to the literature, abscesses can be detected on computed tomography in approximately 15 % of patients with acute diverticulitis [39,40]. In the case of larger abscesses > 4 cm, abscess drainage in combination with antibiotic therapy should be performed to prevent the need for emergency surgery.…”
mentioning
confidence: 99%
“…In the case of larger abscesses > 4 cm, abscess drainage in combination with antibiotic therapy should be performed to prevent the need for emergency surgery. Smaller abscesses less than 3 -4 cm can be cured in almost all cases by antibiotics alone [40]. There is a case control study in which the results for patients treated solely with antibiotic treatment in the case of abscesses that cannot be punctured were not inferior to the results of combined treatment via CT-guided drainage system plus antibiotics in the further clinical course [41].…”
mentioning
confidence: 99%
“…2,3 Studies have shown that the incidence of an abscess complicating an episode of diverticulitis ranges from 17-19%. [4][5][6] The American Society of Colon and Rectal Surgeons recommended that small mesocolic abscesses can be treated with intravenous antibiotics. 7,8 In contrast, large abscesses may be drained percutaneously or by an open procedure.…”
mentioning
confidence: 99%
“…This must be followed by referral for surgical treatment, if needed. The development of this technique allows avoiding multistage surgical procedures (14).…”
Section: Discussionmentioning
confidence: 99%